2007
DOI: 10.1007/s11258-007-9292-y
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Fraxinus excelsior seedlings to grass-induced above- and below-ground competition

Abstract: The competitive interactions between woody seedlings and herbaceous vegetation have received increasing interest in recent years. However, little is known about the relative contributions and underlying mechanisms of above-and below-ground competition between species. We used a novel experimental approach to assess the responses of Fraxinus excelsior seedlings to different combinations of root and shoot competition imposed by the grass Dactylis glomerata under greenhouse conditions. Seedling growth was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 63 publications
(65 reference statements)
2
30
0
1
Order By: Relevance
“…Belowground competition can be intense (Casper andJackson 1997, Bloor et al 2008) and has been demonstrated for both saplings and adult trees in other contexts (Bloor et al 2008, Montgomery et al 2010. Because understory vegetation represents an important fraction of forest biomass (Knight et al 2009, Heckel et al 2010 and is a substantial contributor to ecosystem transpiration (Yepez et al 2003), competition for water and nutrients may be important in structuring forest communities and could be strongly influenced by deer herbivory.…”
Section: Discussionmentioning
confidence: 99%
“…Belowground competition can be intense (Casper andJackson 1997, Bloor et al 2008) and has been demonstrated for both saplings and adult trees in other contexts (Bloor et al 2008, Montgomery et al 2010. Because understory vegetation represents an important fraction of forest biomass (Knight et al 2009, Heckel et al 2010 and is a substantial contributor to ecosystem transpiration (Yepez et al 2003), competition for water and nutrients may be important in structuring forest communities and could be strongly influenced by deer herbivory.…”
Section: Discussionmentioning
confidence: 99%
“…Since root development plays a major role in competition among tree individuals (e.g. Leuschner et al 2004;Bloor et al 2008) and in competition between young trees and herbaceous vegetation for limited soil resources (Löf 2000;Coll et al 2003Coll et al , 2004, information about biomass partitioning to roots and root system extension forms the basis for appropriate evaluations of regeneration success.…”
Section: Introductionmentioning
confidence: 99%
“…Van Dobben et al 1999;Beckage and Clark 2003;Ladd and Facelli 2005). These interactions may involve both competitive and facilitative components, and the indirect impact of eutrophication on tree recruitment may hence vary from negative over neutral to positive (Paluch 2005;Baier et al 2007;Bloor et al 2008).…”
Section: Introductionmentioning
confidence: 99%